Clinical characteristics and frequency of autoantibodies in patients with Systemic Lupus Erythematosus who attend the National Hospital in the period 2018 -2023 - Sánchez, Luis Fernando; Montiel-Jarolin, Dora; Jarolin Montiel, Magali; Samudio, Margarita (Medicina Clínica y Social, 2025)
Introduction: Systemic lupus erythematosus (SLE) is characterized by immune system dysfunction and presents renal, dermatological, neuropsychiatric, and cardiovascular symptoms. Biomarkers play a key role in improving SLE diagnosis, evaluation, and control. Objective: To determine the clinical characteristics and frequency of autoantibodies in patients with SLE hospitalized at the National Hospital of Itauguá between 2018 and October 2023. Methodology: Descriptive, observational, cross-sectional study with an analytical component that included patients with SLE hospitalized at the National Hospital of Itauguá. Demographic and clinical characteristics, and the presence of autoantibodies (anti-DNA, anti-Sm, anti-RNP, anti-Ro, anti-La, anti-Jo, rheumatoid factor, anti-ribosomal factor, anti-histone, anticardiolipin, and lupus anticoagulant) were analyzed. Descriptive statistics and the chi square test were used at a significance level of 0.05 to establish associations. Results: 164 patients between 13 and 87 years of age (median: 28.5) were included, 87% were female, 53% from the Central Department. 51.8% of the patients had severe disease activity, among the most frequent manifestations were alopecia (81.7%), arthralgia (75.6%), headache (67.7%), malar erythema (58.5%), arthritis (34.8%) and in the proportion (31,7%) nephritis and prolonged fever. Anti-DNA was present in 59.8% (n=98), FR 23.78% (n=39), anti-Ro 43.90% (n=72), anti-Sm 32.32% (n=53), anti-RNP 23.8% (n=39), anti-La 17.68% (n=29), anti p ribosomal 13.41% (n=22), anti-centromere 4.88% (n=8), anti SL70 2.44% (n=4), anti-histone 9.76% (n=16), anti-cardiolipin 7.3% (n=12), lupus anticoagulant 8.54% (n=14). Anti-DNA, anti-rnp and anti-p ribosomal autoantibodies were significantly associated with nephritis; and anti Sm with Reyunad syndrome. Conclusion. A high prevalence of severe disease activity was identified in SLE patients, with predominant symptoms such as alopecia and arthralgia. The most frequent autoantibodies were anti-DNA, anti-Ro, and anti-Sm, with significant associations with nephritis and Raynaud’s syndrome. These findings highlight the importance of biomarkers in SLE management.
Keywords: Systemic lupus erythematosus; autoantibodies; clinical manifestations